Productive performance and qualitative egg characteristics of two local lines chickens and laying brown Lohmann - Tawfiq, Isra Mubashshir; al-Nuaymi, Majid Ahmad Sabri (مجلة العلوم الزراعية و البيئية و البيطرية : مجلة علمية محكمة ربع سنوية., 2022)
This study was conducted to compare the productive performance of two local lines chickens (black and brown- feathered chickens) and laying brown Lohmann strain for the period from 4- 6 months of age. The birds were divided into three treatments, the first treatment Local black, the second local brown, and the third brown Lohmann, with 15 females and 3 males from each group divided into three replicates (1 ♂: 5 ♀).The following characteristics were studied: live body weight, age of sexual maturity, weight of the first egg, average weight of eggs, egg production % HD, egg mass, feed conversion ratio and egg specific characteristics for the three groups. The results indicated that there were significant differences (P < 0.05) in the characteristic of live body weight at sexual maturity and at 6 months of age in favor of brown Lohmann, which was 1207.2, 1032.1, 1109. 7 g and 1379.6, 1207.4, 1219.8 for the Lohmann brown chicken, local brown chicken and black local chicken. Also, the brown Lohmann chickens showed the lowest age of sexual maturity of 138.13 days, which was significantly (P < 0.05) superior to the local brown chickens' 143.00 days, which in turn was significantly superior to the black local chickens 148.33 days. The black local chickens achieved a significant (P<0.05) superiority in the weight of the first egg and egg weight compared to the local brown and brown Lohman chickens. As for the number of eggs produced/female, egg mass, HD% egg production and feed conversion efficiency egg shape index, the brown Lohman outperformed the local chickens. As for the albumen weight, shell thickness, the local black and Lohmann chickens outperformed the local brown chickens. As for the characteristic of high yolk and yolk weight, the local chickens of both types were superior to the Lohmann strain. As for the characteristic of high whiteness, the local brown and brown Lohmann chickens outperformed the black local chickens. As for the egg length the local black and local brown outperformed the Lohmann chickens. while the shell weight was no significant differences between the three groups.